N, S Dual Doped Mesoporous Carbon Supported Co9S8 Nanoparticles as Efficient Hydrogen Evolving Electrocatalysts in a Wide pH Range. Issue 35 (17th September 2021) - Miao, Sijia; Xu, Jing; Tang, Duihai; Zhang, Wenting; Wang, Yichen; Huang, Yuan; Wang, Jianjun; Zhao, Zhen; Xin, Shigang
Abstract: A series of Co9 S8 nanoparticles (NPs) embedded, N, S co‐doped mesoporous carbons were synthesized by the combination of evaporation induced self‐assembly (EISA) method and simple pyrolysis method. Melamine formaldehyde (MF) resin was used as carbon and nitrogen precursor. CoCl2 and thiourea were utilized as cobalt and sulfur precursors, respectively. The as‐obtained samples possessed mesoporous structure. The optimized sample of MF4.0T6.0 exhibited excellent electrochemical performance towards hydrogen evolution reaction (HER) in wide pH range, which achieved a current density of 10 mA cm‐2 at 163 mV (pH 0), 149 mV (pH 14), and 325 mV (pH 7). Abstract : A series of Co9 S8 nanoparticles embedded, N, S co‐doped mesoporous carbons were synthesized by the combination of evaporation induced self‐assembly method and simple pyrolysis method. Melamine formaldehyde resin was used as carbon and nitrogen precursor. CoCl2 and thiourea were utilized as cobalt and sulfur precursors, respectively. The obtained catalyst exhibits excellent performance for hydrogen evolution reaction at all pH values.